Analysis of Production Cost Determination Using the Job Order Costing Method in Setting the Selling Price at Bengkel Bubut Lestari Jaya - Lismayanti, Lismayanti; Kusmilawaty, Kusmilawaty; Syafina, Laylan (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to find out the calculation of the cost of production of the Lestari Jaya Lathe Workshop using the Job Order Costing method during May 2023 and make an order cost card. The Lestari Jaya Lathe Workshop does not calculate the cost of production accurately. Research on the analysis of the cost of production based on the Job Order Costing method uses a qualitative descriptive approach research method. The results of the study showed that there was a difference in results. The calculation of the cost of production using the company's method with the Job Order Costing method has a difference of IDR 3,633,268, -. For the calculation of the selling price there is a difference of IDR 3,996,595, -. The calculation of the company's cost of production is smaller than the cost of production with the Job Order Costing method so that the profit generated is lower.